Vozes da África no português angolano e brasileiro: conexões, semelhanças e construção de um vocabulário digital - Silva, Josimar Santana (2025)
The contact between the native African languages and Portuguese, resulting from colonization and slavery, played an important role in the formation of varieties of Brazilian and Angolan Portuguese and other varieties spoken within the framework of African countries of Portuguese official language. Thinking about this, the research problem of this thesis focuses on identifying similarities between the lexicon of African origin present in the Portuguese spoken in Luanda-Angola and that spoken in the quilombola community Mussuca, in the state of Sergipe, Brazil. It is assumed that the linguistic contact made possible the conservation, until today, of some traditional African meanings, also generating similarities between the analyzed varieties. In both cases, the native African languages had or still have an active role in the formation of these varieties of Portuguese. However, due to the contact situation, some lexias may have suffered linguistic influences, which led to different meanings from traditional ones. The research presented as a general objective to analyze and compare the lexias of African origin present in the variety of Portuguese spoken in Luanda and in the variety of Portuguese spoken in the community Mussuca, in order to contribute to studies on the understanding of the roots of non-European varieties of Portuguese. It also presented the following specific objectives: a) to catalogue the lexias of African bases present in the Portuguese spoken in the community of Mussuca-OSE and Luanda-AO; b) explain the contributions of the lexicon of African origin in the constitution of Brazilian and Angolan Portuguese; c) compare lexias of African origin spoken in Luanda-Angola with the lexicon of African origin spoken in the community of MussucaSE; d) build a digital vocabulary with the lexias of African origin found in corpora (available at www.glosafrica.com.br). To carry out the research, two corpora were used, collections of the following research projects: "In search of the roots of Brazilian Portuguese", constituted in Luanda in 2008 and 2013, and "Characterization of popular Portuguese spoken in Afro-Brazilian rural communities of Bahia and Sergipe: documentation of communities of Afro-Brazilian practices for the study of linguistic contacts", recorded in the quilombola community Mussuca, in the state of Sergipe. The methodology was based on the premises of modern lexicography, that is, corpora and appropriate computer programs were used for the survey and subsequent calculation of the data found. For data collection, we took into account the lexias recorded in the works of Castro (2001; 2002), Houaiss, Villar and Franco (2008) and the dictionary of kimbundu-Portuguese, by Assis Júnior (1947). 77 lexias of African origin were found in the analyzed corpora, showing that, since there are lexias of native African languages present in Angolan and Brazilian Portuguese, it was also shown that some but others have shown a different meaning, depending on the context in which they are employed. It was concluded that the linguistic contact, especially in the historical context of European colonization in Brazilian and Angolan territory, played a crucial role in the formation of the variants of Portuguese spoken in Angola and Brazil.